Evaluación del proceso de elaboración de salchicha tipo Cocktel a partir de visceras de bovinos como parte de su formulación - Macias Esparza, Julio César (2012)
The present investigation project (EVALUATION OF THE PROCESS OF ELABORATION OF SAUSAGES TYPE COCKTEL to LEAVE OF VISCERA OF BOVINE AS PART OF THEIR FORMULATION), he was carried out keeping in mind the little industrialization of the viscera of bovine to transform them in elaborated product giving them an added value. In this project thought about an experimental design AxBxC (2x4x2) with 2 repetitions for treatment, being the factor A = agglutinant type in which you uses wheat flour and potato starch; factor B = viscera type using lung, heart, windpipe and it mixes of the three viscera; and factor C = viscera percentage, employee by 50 and 100 percent. In this investigation it is wanted to know the influence of the study factors on the characteristic organoleptic: color, flavor, scent and texture besides the defects and acceptability; and physical - chemical as: humidity, protein, fat, ashes and pH. To evaluate the study factors and their respective levels the test of Multiple Ranges it was executed from Tukey to 5%. For their profiles organoleptic and physical analysis - chemical the best treatment was the T3: wheat flour + heart of bovine + 50 viscera% added in relation to the meat. ............................ ..................